Adopting Mobile Assisted Language Learning to Improve Digital Literacy in the Era of Society 5.0 - Aini Nurul; Afrilia Nur Sitha; Radhia and Fathy (E3S Web of Conferences, 2023)
The industrial and social development from Industry 4.0 to Society 5.0 has brought many challenges, especially regarding the low quality of human resources, which can be overcome by increasing digital literacy. In order to support the programs conducted by the Indonesian government in increasing digital literacy, this study aims to propose the concept of digital literacy learning, especially in digital consumption through portable devices, by adopting the concept of mobile assisted language learning (MALL). The focus of this study is on increasing digital literacy among higher education students as digital literacy is crucial in supporting their learning process and future self-development. The design process of MALL is carried out using the Design Thinking approach. The research respondents were Business and IT students from BINUS Semarang. The research resulted in the concept of a mobile device-based pocket dictionary application for digital literacy learning. Furthermore, the prototype can be developed into a mobile app on the Android platform and web pages that can be accessed anytime and anywhere. Further research can be conducted to provide alternative solutions related to the same issue by using other methods such as Design Sprint and Agile development.